Beispiel Nr: 06
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ -2 x -8 + 0 z=1\\ 1 x +4 y + 0 z=-\frac{1}{2}\\ 8 x -2 y + -1 z=8\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} -2x-8y=1 \\ x+4y=-\frac{1}{2} \\ 8x-2y -z=8 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & -8 & 0 & 1 \\ 1 & 4 & 0 & -\frac{1}{2} \\ 8 & -2 & -1 & 8 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot (-2)\text{-Zeile}1\cdot 1 \\z2s1=1\cdot -2-(-2)\cdot 1 =0 \\ z2s2=4\cdot -2-(-8)\cdot 1 =0 \\ z2s3=0\cdot -2-0\cdot 1 =0 \\ z2s4=(-\frac{1}{2})\cdot -2-1\cdot 1 =0 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & -8 & 0 & 1 \\ 0 & 0 & 0 & 0 \\ 8 & -2 & -1 & 8 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-2)\text{-Zeile}1\cdot 8 \\z3s1=8\cdot -2-(-2)\cdot 8 =0 \\ z3s2=(-2)\cdot -2-(-8)\cdot 8 =68 \\ z3s3=(-1)\cdot -2-0\cdot 8 =2 \\ z3s4=8\cdot -2-1\cdot 8 =-24 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & -8 & 0 & 1 \\ 0 & 0 & 0 & 0 \\ 0 & 68 & 2 & -24 \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeilen vertauschen } \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & -8 & 0 & 1 \\ 0 & 68 & 2 & -24 \\ 0 & 0 & 0 & 0 \\ \end{array} \\ \\ \\ L= unendlich$